2021
DOI: 10.1038/s41598-021-98542-3
|View full text |Cite
|
Sign up to set email alerts
|

A differential DNA methylome signature of pulmonary immune cells from individuals converting to latent tuberculosis infection

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis, spreads via aerosols and the first encounter with the immune system is with the pulmonary-resident immune cells. The role of epigenetic regulations in the immune cells is emerging and we have previously shown that macrophages capacity to kill M. tuberculosis is reflected in the DNA methylome. The aim of this study was to investigate epigenetic modifications in alveolar macrophages and T cells in a cohort of medical students with an increased risk of TB e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The infection status of such controls was unknown. As has been reported by a longitudinal study which found healthy subjects who later developed LTBI had a unique DNA methylation profile ( 23 ), the aberrant DNA-methylated genes detected in aforementioned studied might confounded by LTBI status of the controls because of the complex immune progress from TB infection to active disease. Esterhuyse et al ( 24 ) incorporated dmCpGs from only monocytes and granulocytes by machine learning to distinguish active TB from LTBI in cross-sectional design and obtained a model with an AUC of 0.74, which was consistent with our results.…”
Section: Discussionmentioning
confidence: 74%
“…The infection status of such controls was unknown. As has been reported by a longitudinal study which found healthy subjects who later developed LTBI had a unique DNA methylation profile ( 23 ), the aberrant DNA-methylated genes detected in aforementioned studied might confounded by LTBI status of the controls because of the complex immune progress from TB infection to active disease. Esterhuyse et al ( 24 ) incorporated dmCpGs from only monocytes and granulocytes by machine learning to distinguish active TB from LTBI in cross-sectional design and obtained a model with an AUC of 0.74, which was consistent with our results.…”
Section: Discussionmentioning
confidence: 74%
“…There is growing evidence to suggest that viral and bacterial infections can lead to epigenetic changes in the host, which can affect the host's immune response and the severity of the infection [121][122][123]. Epigenetic changes refer to alterations in the way genes are expressed rather than changes in the underlying DNA sequence itself [124].…”
Section: Epigenetic Responsementioning
confidence: 99%
“…Indeed, a global methylation analysis showed that there existed over 1000 differentially methylated regions between PBMCs of tuberculosis (TB) patients and healthy controls, and there were still almost 4000 differentially methylated regions following completion of anti-TB treatment, and the majority of the affected genes were associated with the autophagy pathway [37,38]. Similarly, a distinct DNA methylation profile, which was enriched in the pentose phosphate pathway, T cell migration and IFN-γ production pathways, was uncovered in alveolar macrophages (AMs) after M. tuberculosis infection [39]. Intriguingly, there were more differentially methylated regions in AMs than in PMBCs within the same individual [38].…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%